Generalized Multiprotocol Label Switching convergence NETWORKS IN THE SCHEME - Eriek Eriek Orlando (Majalah SIKOMTEK, 2005)
Convergence of Internet and telecommunications, with applications in it that more and morebandwidth with QoS penqaturan it finally takes the network and element in it which gave fullsupport to the preservation and improvement of network performance. If the first object thatbandwidth is always a predictable, so this time some applications already require schemes